Developing student-centered assessment for a postgraduate course designed for Basic Education Teachers - Daniel Guilherme Gomes Sasaki; Sisko Mällinen (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
The Constructive Alignment theory, by Biggs, relies on students' self-construction of meaning by relevant learning activities. To accomplish this goal, teachers have to align four essential elements: curriculum, Intended Learning Outcomes (ILOs), methodologies and assessment. In this paper, we describe an implementation of a constructively aligned postgraduate course on active learning methodologies for basic education teachers. The syllabus was comprised of four well-established active learning methods: Predict-Observe-Explain (POE), Peer Instruction (PI), Jigsaw and Six Thinking Hats (STH). Students had to plan, discuss in pairs, perform a real active lesson with their own pupils and observe and provide peer feedback to their colleague. Assessment was carried out as the following forms: self-reflection, active lesson plan, peer assessment and self-assessment and one summative form: active lesson report. Each assessment evaluated distinct skills related to both specifics ILOs and learning activities. The results reveal that aligned assessment fostered learning, encouraged self and peer reflection, improved teacher feedback and promoted an effective collaboration among students.